Gaya Bahasa Repetisi Dalam Tindak Tutur Asertif Pada Wacana Debat Keempat Calon Wakil Presiden Indonesia 2024 - Sunarni, Nani; Indrayani, Lia Maulia; Erlina, Erlina; Firmansyah, Eka Kurnia (Fakultas Seni Rupa dan Desain ITB, 2025)
This study investigates the role of repetition as a linguistic strategy in assertive speech acts within the debate discourse of the fourth vice-presidential candidates leading up to the 2024 election. Specifically, it examines the thematic relationships between repetitive figures of speech and assertive speech acts used by the first, second, and third vice-presidential candidates, utilizing NVivo 12 Plus for data visualization. Adopting a qualitative descriptive method, the study identifies instances of repetition in assertive speech acts, categorizing them into two primary functions: